Optimization of Grid-Connected PV System Design Integrated with BESS for Green Hydrogen Production Using PVsyst at PT PLN Nusantara Power UP Gresik - Wahyudi , Muhammad Lukman; Arifin, Zainal (Journal of Authentic Research, 2026)
The increasing demand for clean energy and the urgency of achieving Indonesia’s Nationally Determined Contribution (NDC) targets and the 2060 Net Zero Emission commitment highlight the need for reliable renewable-based power systems to support emerging green hydrogen development. Hydrogen is recognized as a strategic energy carrier for decarbonizing hard-to-abate industrial sectors, thereby increasing the importance of stable renewable electricity supply for electrolysis processes. This study aims to design and analyze a Solar Photovoltaic (PV) system integrated with a Battery Energy Storage System (BESS) as the primary electricity source for the hydrogen electrolysis process at PT. PLN Nusantara Power Unit Pembangkitan Gresik. A quantitative approach was employed through load assessment, technical modeling of the PV and storage systems, and simulation using PVsyst software. The results indicate that a 1,252 kWp PV system can deliver an annual energy output of 1,362 MWh, achieving a specific yield of 1,088 kWh/kWp/year and a Performance Ratio of 56.93%. This production closely matches the annual energy demand of the hydrogen plant, which reaches 1,414.2 MWh. Consequently, the integration of a BESS is essential to maintain supply continuity during periods of reduced solar irradiance and to stabilize power input to the electrolyzer. The findings demonstrate that the proposed PV–BESS configuration significantly increases the contribution of renewable energy, reduces dependency on the grid, and supports the sustained production of low-carbon hydrogen. Practically, this study provides a scalable technical model for integrating solar and storage systems to accelerate green hydrogen deployment in Indonesia, particularly within industrial power generation facilities.